The immune system and serum glutamine during a triathlon - Rohde, T.; MacLean, D. A.; Hartkopp, A.; Pedersen, B. K. (European Journal of Applied Physiology, 1996)
This study confirms that prolonged endurance exercise results in changes in the cytotoxic function of the NK and LAK cells as well as the proliferative response. The time-course of changes in serum glutamine concentrations were best parallelled by changes in LAK cell activities.